The Future of Learning and Training in an Augmented Reality - Kangdon Lee (Park University, 2012)
Students acquire knowledge and skills through different modes of instruction that include classroom lectures with textbooks, computers, and the like. The availability and choice of learning innovation depends on the individual's access to technologies and on the infrastructure environment of the surrounding community. In this rapidly changing society, information needs to be adopted and applied at the right time and right place to maintain efficiency in all settings. Augmented reality is one technology that dramatically shifts the timing and location of learning. This paper describes augmented reality, how it applies to learning, and its potential impact on future education.